STRUKTUR POPULASI DAN LAJU SILANG DALAM PER GENERASI AYAM KAMPUNG DI KECAMATAN TELUK AMBON - Rajab Rajab; Bercomien Juliet Papilaya (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2019)
The objective of this research was to know both the population structure and the inbreeding rate per generation of native fowl in Teluk Ambon District Ambon Regency. This study was conducted by using survey method with purposive random sampling of 60 farmers/breeders from Tawiri, Hatiwe Besar and Wayame villages. The variables observed were the number of adult male chicks (Nm), number of adult female chicks (Nf), number of young male and young female chicks, actual population size (Na), effective population size (Ne), and the rate of inbreeding per generation (Î”F). The results showed that structure population of the domectic fowl in Teluk Ambon district include the number of adult male chicks 558 tail (8,17 %), young male chicks 1031 tail (15,10 %), male of DOC 1486 tail (21,76 %), whereas the number of female were 1451 tail (21,25 %), 1176 tail (17,22 %), and 1126 tail (16,49 %) respectively for adult, young and DOC. Actual population size of domestic fowl was 2009 tail and the size of population effective was 1612 tail. The rate of inbreeding per generation was 0.000310 %.